DESIGN, SYNTHESIS, AND EVALUATION OF NEW DERIVATIVE OF 1,2,4-TRIAZOLES FOR ANTIMICROBIAL AND ANTI-INFLAMMATORY ACTIVITY - Jalihal, Prabhu C.; Rajoriya, Vaibhav; Kashaw, Varsha (International Journal of Current Pharmaceutical Research, 2018)
Objective: The object of the study is to design, synthesize and biological evaluation of isoniazid derived 1,2,4-triazoles compounds. Methods: Isoniazid based 1,2,4-triazoles derivatives have been synthesized by reaction of Isoniazid with carbon disulfide in basic medium (KOH) to form Potassium dithiocarbazinate salt and reaction with hydrazine hydrate converted into 4-amino-5-(pyridin-4-yl)-4H-1,2,4-triazole-3-thiol. These compounds were reacted with seven different benzaldehyde to form 4-[(substituted phenyl)-methylene]-amino-5-(pyridine-4-yl)-4H-1,2,4-triazol-3-thiol (4). The final compounds were synthesized by reaction with four different acetanilide to form 4-[substituted phenyl)-methylene]-amino-3-(N-substitutedcarboxamidomethylthio)-5-(pyridine-4-yl)-4H-1,2,4-triazoles derivatives. All these compounds were characterized by IR, 1H-NMR, [13]C-NMR and elemental analysis. The antimicrobial activity was determined by the cup plate method. Acute anti-inflammatory activity determined by using carrageenan-induced rat paw edema model. Results: Series PJ-A4, PJ-A7 and PJ-A13 showed more than 90% of the zone of inhibition against both Gram positive and Gram negative organisms. The antifungal study suggested that among synthesized compounds series PJ-A4, A7, A9, A11 and A13 showed more than 90% of zone of inhibition, A2, A10 and A12 shows more than 80% of the zone of inhibition. Anti-inflammatory study data indicate that compounds PJ-A4, PJ-A8, PJ-A9 and PJ-A13 produced 70 to 76% of paw edema inhibition compare to standard drug Ibuprofen which showed 83.3% after 5 h. Conclusion: Results suggested that the isoniazid based 1,2,4-triazole derivatives have significant antibacterial, antifungal and anti-inflammatory activity.